Vaccination and the politics of exclusion: The unintended consequences of Covid-19 response - Anton Novenanto; Nindyo Budi Kumoro; Yuni Kurniawaty; Laila Azkia; Rusli Effendi; Anastasya Kareth; I Wayan Suyadnya (Universitas Airlangga, 2026)
This study investigates how Indonesia’s Covid-19 vaccination campaign, while framed as a public health solution, inadvertently reinforced and reconfigured existing structures of marginalization. Drawing on collaborative ethnographic research conducted across four diverse sites—Surabaya, Banjarmasin, Jambi, and Jayapura—between September and November 2021, the study explores how crisis response mechanisms intersect with socio-spatial vulnerabilities. Using a political economy and disaster studies framework, the research conceptualizes marginality not as a static condition but as a dynamic process shaped by governance failures, cultural dissonance, and infrastructural inequities. This study employed a collaborative ethnographic approach, involving local researchers and digital coordination tools to document the lived experiences of healthcare workers, students, Indigenous communities, and religious groups. Data were collected through participant observation, interviews, and community engagement, focusing on how vaccine rollout strategies were perceived, resisted, or adapted locally. Findings reveal that vaccination programs often deepened exclusion: healthcare workers faced institutional neglect; students were deployed without adequate protection; Indigenous groups were overlooked or stigmatized; and religious communities contested biomedical narratives. These cases illustrate how technocratic crisis responses can reproduce systemic inequalities under the guise of resilience. The paper concludes that Indonesia’s pandemic governance prioritized control over care, transforming public health infrastructures into a mechanism of exclusion. It calls for a reorientation of disaster studies toward understanding vulnerability as a product of political and spatial dynamics, and urges more inclusive and context-sensitive crisis interventions.